Why inclusive education remained stagnant in Pidie regency? - Nabila, Nudhar; Niswanto, Niswanto; Bahrun , Bahrun; Wardatina, Wardatina (Universitas Jambi, Indonesia, 2026)
Inclusive education is a manifestation of the global commitment to education for all. Although mandated by various national regulations, the implementation of inclusive education remained stagnant due to multiple challenges. This study aimed to examine strategies adopted by the government in planning and ensuring the effectiveness of inclusive education in Pidie Regency. This study employed a qualitative approach involving data from the education data system (Dapodik) and key stakeholders from Balai Penjaminan Mutu Pendidikan (BPMP) Aceh, Dinas Pendidikan dan Kebudayaan Kabupaten Pidie (Disdikbud Pidie), SMPN 4 Sigli, and SDN 1 Lampoih Saka. The qualitative data were processed and analyzed using NVivo 15 to facilitate systematic coding, theme categorization, and identification of patterns related to the implementation of inclusive education. The study found that the main challenges in implementing inclusive education are the lack of indicators of success, limited human resources, limited literacy about inclusive education, the absence of clear regulations, lack of coordination, limited access to infrastructure, and budget constraints. These results indicated that inclusive education in Pidie regency remains stagnant due to weak policy support and unstructured practices. This pointed out the need to strengthen policies and regulations, enhance resources and facilities, and build sustainable capacity to ensure the effective and equitable implementation of inclusive education.